Tamanho da unidade experimental básica e tamanho de parcela para a massa verde de crotalária juncea - Facco, Giovani (2016)
This study aimed to investigate the influence of the basic experimental unit size in the estimate of the plot size to evaluate the fresh matter of aerial part of brown hemp (Crotalaria juncea L.), using three different methods for determining the plot size. Two uniformity trials were carried out in the field during the 2014/2015 agricultural year. Uniformity trials with useful area of 1152m2 were sown on October 22, 2014 and on December 03, 2014, in the experimental area of the Plant Science Department of the Federal University of Santa Maria. For both sowing dates, the 48m×24m (1152m2) area was evaluated in basic experimental units (BEU) of 0.5m×0.5m (0.25m2), totaling 4608 BEU for each sowing date. For each sowing date, the harvest was carried out during the crop flowering period. From the obtainment of fresh matter values of aerial part of brown hemp plants of each BEU, different plans were simulated with different sizes of BEU in order to determinate the plot size. Plot size was determined for each organized BEU size by three different methods: method of maximum curvature of the coefficient of variation model, the modified maximum curvature method and Hatheway method. For the method of maximum curvature of the coefficient of variation model, 64 plans were simulated with BEU ranging from 0.25m2 to 64m2. For the modified maximum curvature method, 36 plans were simulated with BEU ranging from 0.25m2 to 16m2 and for the Hatheway method (1961), 36 plans were simulated with BEU ranging from 0.25m2 to 16m2. The estimate of the optimum plot size to evaluate the fresh matter of brown hemp depends on the basic experimental unit size but it is independent of the method utilized to determine the plot size. Assessing the fresh matter in basic experimental units as small as possible is recommended in order to use it in the estimation of the optimum plot size.